Lower risk of invasive meningococcal disease during pregnancy: national prospective surveillance in England, 2011–2014. (8th May 2019) - Parikh, SR; Borrow, R; Ramsay, ME; Ladhani, SN
Abstract : Objective: To describe cases of invasive meningococcal disease (IMD) in women of childbearing age and to estimate the disease incidence and relative risk of IMD in pregnant compared with non‐pregnant women. Design: Prospective enhanced national surveillance for IMD. Setting: England. Population: Women of reproductive age (15–44 years) with laboratory‐confirmed IMD. Methods: Public Health England conducts enhanced national surveillance for IMD in England. Laboratory‐confirmed cases are followed up with postal questionnaires to general practitioners. All cases confirmed in women of reproductive age from 1 January 2011 to 31 December 2014 were included. Main outcome measures: Annual IMD incidence and relative risk of IMD in pregnant compared with non‐pregnant women of reproductive age. Results: During the 4‐year surveillance period, there were 1502 cases of IMD in females across England; of these, 310 (20.6%) cases were in women of reproductive age, including four women who were pregnant at the time of IMD confirmation (1.3%). Serogroup distribution of IMD cases in women of childbearing age was similar to the overall distribution. The four cases in otherwise healthy pregnant women were confirmed across all trimesters and all survived; one case in the first trimester had a septic miscarriage. The incidence of IMD was lower in pregnant than in non‐pregnant women (0.16 compared with 0.76 per 100 000 pregnant and non‐pregnant years, respectively), giving a lower risk of IMD in pregnant women (incidence rate ratio, IRR, 0.21; 95% confidence interval, 0.06–0.54). Conclusions: Pregnant women are nearly five times less likely to develop IMD compared with non‐pregnant women, but the infection can be severe. Tweetable abstract: The risk of meningococcal disease is lower in pregnant women compared with non‐pregnant women; the infection can occur across all trimesters and can be severe. Tweetable abstract: The risk of meningococcal disease is lower in pregnant women compared with non‐pregnant women; the infection can occur across all trimesters and can be severe.